Introducing planar hydrophobic groups into an alkyl-sulfonated rigid polyimide and how this affects morphology and proton conductivity. (20th March 2019) - Nagao, Yuki; Tanaka, Teppei; Ono, Yutaro; Suetsugu, Kota; Hara, Mitsuo; Wang, Guangtong; Nagano, Shusaku; Abe, Takashi
Abstract: Effects on organized structure and proton conductivity by the introduction of hydrophobic groups into the sulfonated polyimide backbone were investigated. A new sulfonated random co-polyimide with ion exchange capacity (IEC) of 2.69 meq. g −1 was synthesized. In our previous reports, we demonstrated that alkyl-sulfonated polyimide (ASPI-2, IEC = 3.11 meq. g −1 ) thin film consisting of pyromellitic dianhydride and 3, 3′-bis(3-sulfopropoxy)benzidine exhibits the organized lamellar structure and high in-plane proton conduction over 10 −1 S cm −1 based on a lyotropic liquid crystalline (LC) property. However, the origin of the lyotropic LC property in the sulfonated polyimide thin films was not clear. In this paper, 20% hydrophobic o-tolidine was introduced into the ASPI-2 polymer backbone to suppress the lyotropic LC property. To discuss the effect on the organized structure and proton conductivity by the introduction of the hydrophobic groups, domain size, internal nanostructure, proton conductivity, water uptake, and proton dissociation from sulfonic acid groups were investigated by polarized optical microscopy, grazing incidence small-angle X-ray scattering, impedance measurements, quartz crystal microbalance, and Fourier transform infrared spectroscopy. The random co-polyimide thin film exhibited the birefringence and in-plane oriented lamellar structure. The lamellar distance was expanded up to 3.0 nm by water uptake. The lamellar expansion, molecular ordering, and proton dissociation showed similar behaviors by water uptake compared to the previous ASPI-2 thin film. Proton conductivity and water uptake per sulfonic acid group exhibited relatively high value of 3.2 × 10 −2 S cm −1 and 12.5 at relative humidity (RH) = 95% and 298 K. The estimated mobility of proton carriers decreased by 74% at λ = 12.5. Results suggest that the 20% substitution by hydrophobic monomers does not affect the structural difference but leads to the strong mobility decrease of proton carriers rather than the decrease of number of density. Graphical abstract: Image 10566 Highlights: Some sulfonated polyimide thin films exhibit organized lamellar structure. Lamellar structure exhibits high in-plane proton conductivity. In this paper, 20% hydrophobic backbone was randomly introduced. Thin film still showed organized lamellar structure and relatively high conductivity. Mobility of proton carriers was discussed based on the structural similarity.